Homologacija elementov prototipnega vozila - Kostanjevec, Andrej (Strojniški vestnik, 1999)
For a vehicle to be registered for use in Slovenia it is necessary to obtain a motor vehicle approval document. In the case of manufacturing a unique prototype vehicle it is the task of the manufacturer to provide all the necessary certificates relating to the strength and/or functional suitability of the built-in elements. This paper presents strength calculations on the chasis elements of the Šinkovec MM vehicle. In order to obtain the data on possible loads acting on the wheels, a multi-mass dynamic model of the vehicle has been developed and on the basis of the simulation of roads under-different driving conditions these loads were then calculated. They were then applied to elements of the front and rear suspension, and a computer supported strength analysis of the elements was made. The possibility of both instant and fatique failure of the discussed elements was verified.
Keywords: vozila; podvozja vozil; izračuni trdnostni; homologacija; konstruiranje; podvozje; trdnost